Local and Intravenous Anesthesia for Thoracic Endovascular Aortic Repair: 8 Years Experiences - Furui, Masato; Sakaguchi, Shoji; Kakii, Bunpachi; Uchino, Gaku; Asanuma, Mai; Suzuki, Haruo; Yoshida, Takeshi (Cardiology and Cardiovascular Medicine, 2020)
Background: General anesthesia is popular in the management of thoracic endovascular aortic repair (TEVAR). However, patients who undergo TEVAR are often elderly, with low activity or low respiratory function; therefore, less invasive anesthesia is considered. This study aimed to verify the safety and efficacy of local and intravenous anesthesia for TEVAR. Methods and Results: From December 2010 to October 2017, 148 patients with an arch or descending aortic aneurysm underwent TEVAR in our hospital. Of these, 70 patients (38 males; mean age, 71±12 years) underwent TEVAR with local and intravenous anesthesia. We retrospectively examined the intraoperative difficulties due to patients’ movement, respiratory control, incidence of conversion to general anesthesia, and extension of procedure time by more than 2 minutes. Although 36 patients (51.4%) required additional sedation or analgesic administration due to patients’ movement or pain, the procedure time did not extend beyond 2 minutes for any patient. All procedures were completed without conversion to general anesthesia. A major complication, cerebral infarction, was noted in 1 patient (1.4%). For 5 patients (7.1%), the access route for TEVAR was narrow, and the iliac artery was dissected. This complication was easy to detect due to the patients’ perception of pain. Conclusion: TEVAR with local and intravenous anesthesia was performed without difficulty and was advantageous due to the early detection of complications. This anesthetic management is less invasive and may be optimal for TEVAR in the elderly or other populations where full sedation is contraindicated.